2015
DOI: 10.1002/2015gb005134
|View full text |Cite
|
Sign up to set email alerts
|

Small phytoplankton drive high summertime carbon and nutrient export in the Gulf of California and Eastern Tropical North Pacific

Abstract: Summertime carbon, nitrogen, and biogenic silica export was examined using 234 Th:238 U disequilibria combined with free floating sediment traps and fine scale water column sampling with in situ pumps (ISP) within the Eastern Tropical North Pacific and the Gulf of California. Fine scale ISP sampling provides evidence that in this system, particulate carbon (PC) and particulate nitrogen (PN) concentrations were more rapidly attenuated relative to 234 Th activities in small particles compared to large particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 140 publications
(214 reference statements)
7
70
0
Order By: Relevance
“…It has been shown recently that the performance of the Siegel et al (2014) export flux model improves substantially if the parameters are regionally tuned supporting the importance of food web structure (Stukel et al, 2015). Further, recent field data summaries show strong relationships between the vertical scales of sinking flux attenuation in the TZ and both phytoplankton community structure in the EZ (Guidi et al, 2015;Puigcorbé et al, 2015) and environmental conditions in the TZ (Marsay et al, 2015). The explicit testing of the hypothesis and development of modeling tools to diagnose carbon cycling processes will require an extensive data set of a wide range of ECC states.…”
Section: Carbon Export From the Euphotic Zone And Its Fate Within Thementioning
confidence: 95%
“…It has been shown recently that the performance of the Siegel et al (2014) export flux model improves substantially if the parameters are regionally tuned supporting the importance of food web structure (Stukel et al, 2015). Further, recent field data summaries show strong relationships between the vertical scales of sinking flux attenuation in the TZ and both phytoplankton community structure in the EZ (Guidi et al, 2015;Puigcorbé et al, 2015) and environmental conditions in the TZ (Marsay et al, 2015). The explicit testing of the hypothesis and development of modeling tools to diagnose carbon cycling processes will require an extensive data set of a wide range of ECC states.…”
Section: Carbon Export From the Euphotic Zone And Its Fate Within Thementioning
confidence: 95%
“…Recent sediment trap work has suggested that smaller, slow sinking particles could contribute to the overall flux in oligotrophic regions (Durkin et al, 2015;Hung et al, 2012;Puigcorbé et al, 2015). A previous study in the northwestern Pacific also showed elevated Mn in subsurface traps that could have resulted from small, slow sinking…”
Section: On the Use Of Large Versus Small Particle E: 234 Thmentioning
confidence: 96%
“…Zooplankton, phytoplankton and high nutrient levels also reduce POC/PON in coastal waters (Koeve, 2006;Martiny et al, 2013b;Watanabe and Kuwae, 2015;Talmy et al, 2016). The relatively high POC/PON ratio in offshore water is primary caused by small phytoplankton, which is the dominant contributor to POC levels at the ocean surface and has a high POC/PON ratio (Richardson and Jackson, 2007;Puigcorbé et al, 2015). The increase of POC/PON with the distance is very significant in the North Table S4.…”
Section: Variations In Poc Pon and Poc/pon With Offshore Distancementioning
confidence: 99%